2015
DOI: 10.1080/21645515.2015.1008885
|View full text |Cite
|
Sign up to set email alerts
|

Survey on public awareness, attitudes, and barriers for herpes zoster vaccination in South Korea

Abstract: A cross-sectional study was performed to assess current public awareness of herpes zoster (HZ) and its vaccine, determine the factors that influence people's intention regarding HZ vaccination, and investigate the barriers for vaccination by changing decisions with sequential questions regarding knowledge, cost, and physician's recommendation in the Department of Infectious Diseases, Korea University Guro Hospital, in South Korea, between August 23 and September 15 of 2013. Among 603 subjects who completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 22 publications
(33 reference statements)
2
36
2
Order By: Relevance
“…Lack of knowledge regarding HZ was thought to be at the root of these responses. Yang et al 11 performed a survey at a university hospital in South Korea and among 603 patients, 85.7% knew about HZ, a very similar result to our study. They also showed that women, younger age, and those with higher income and higher education levels were more likely to know about HZ.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Lack of knowledge regarding HZ was thought to be at the root of these responses. Yang et al 11 performed a survey at a university hospital in South Korea and among 603 patients, 85.7% knew about HZ, a very similar result to our study. They also showed that women, younger age, and those with higher income and higher education levels were more likely to know about HZ.…”
Section: Discussionsupporting
confidence: 87%
“…Lack of knowledge regarding HZ was thought to be at the root of these responses. Yang et al . performed a survey at a university hospital in South Korea and among 603 patients, 85.7% knew about HZ, a very similar result to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies to assess public awareness of HZ and its vaccination were then carried out. The Herpes Zoster Global Awareness Survey from 22 countries 17 and a knowledge, attitude, and practice study in South Korea 18 were conducted in 2009 and 2015, respectively. Factors promoting or limiting the prevalence of vaccination against HZ were also investigated in the latter study.…”
Section: 對帶狀疱疹的認識、態度與行為:針對五十歲或 以上人士的橫斷面研究mentioning
confidence: 99%
“…Factors promoting or limiting the prevalence of vaccination against HZ were also investigated in the latter study. 18 There has been limited research conducted in the Hong Kong population to assess the knowledge of and attitudes towards HZ and the practice of vaccination. This study aimed to explore these areas.…”
Section: 對帶狀疱疹的認識、態度與行為:針對五十歲或 以上人士的橫斷面研究mentioning
confidence: 99%
“…Both patient and provider barriers, such as high vaccine cost, complex methods of reimbursement and the requirement for freezer storage, have been suggested to explain the poor uptake of zoster vaccine in the USA [90,91]. A survey of public attitudes to zoster vaccine in South Korea found that high vaccine cost and low perceived risk of zoster were the main obstacles to vaccination, although a physician recommending the vaccine could reverse around 70% of vaccine refusals [92]. …”
Section: Development Of a Vaccine Against Zoster Efficacy And Safetymentioning
confidence: 99%